Genetic association of rs373001 polymorphism in mir-130b gene with susceptibility to dyslipidaemia and correlation with lipid profile - Nouman Fakhar; Asifa Majeed; Amir Rashid; Uzma Naeem (Journal of the Pakistan Medical Association, 2026)
Objective: To find the association and correlation of rs373001 polymorphism in micro-ribonucleic acid-130b gene with the risk of dyslipidaemia. Method: The case-control study was conducted from April 2 to December 13, 2024, at the Department of Biochemistry and Molecular Biology, National University of Medical Sciences, Rawalpindi, Pakistan, in collaboration with the Chemical Pathology Laboratory, Army Medical College, Rawalpindi, and comprised dyslipidaemia cases and healthy controls. Genomic deoxyribonucleic acid extraction was done from blood samples using an organic method, and tetra-primer amplification refractory mutation system-polymerase chain reaction, followed by agarose gel electrophoresis. Data regarding lipid profile and fasting blood sugar was noted for all the participants. Data was analysed using SPSS 26. Results: Of the 300 subjects, 150(50%) were in each of the two groups. There were 57% males and 43% females among the cases with mean age was 49.1±11.6 years, and 52% females and 48% males with 43.3±15.6 years among the controls. The rs373001 polymorphism of micro-ribonucleic acid-130b gene showed a C>T transition. The C allele (reference allele) frequency was n=123 (41%) in cases and n=144 (48%) in controls, while T allele (risk allele) frequency was n=177 (59%) in cases and n=156 (52%) in controls. The cases had 120(80%) CT, 1(0.7%) CC and 29(19.3%) TT genotypes, while the controls had 142(94.7%) CT, 1(0.7%) CC and 7(4.7%) TT genotypes. The TT genotype was a risk (adjusted odds ratio: 4.8, p<0.001) in recessive genetic model, while CT was protective (adjusted odds ratio: 0.2, p<0.001) in over-dominant model. A correlation was noted between genotypes and triglycerides levels (p=0.039) without confounders age and gender, but when adjusted with these confounders, no correlation was found (p>0.05). Conclusion: There was a positive association of the TT genotype of rs373001 polymorphism in micro-ribonucleic acid-130b gene with the risk of dyslipidaemia development in recessive genetic model and log-additive pattern of inheritance. Key Words: Low-density lipoprotein, High-density lipoprotein, microRNAs, Polymorphism, Lipid metabolism.